2020
DOI: 10.1371/journal.pone.0230805
|View full text |Cite
|
Sign up to set email alerts
|

The innovation value chain of patents: Breakthrough in the patent commercialization trap in Chinese universities

Abstract: The innovation value chain is an effective tool for analysing innovation activities and reflects the process of value creation and increase in innovation activities. From the perspective of innovation value chains, we divided patent innovation activities into three stages: knowledge innovation stage, applied research stage and patent commercialization stage. The panel data from 64 universities directly managed by the Ministry of Education from 2009 to 2017 were used and several conclusions were drawn: 1) In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…It can not only guide firms' technological innovation, but also stimulate their internal R&D investment enthusiasm and independent innovation capabilities. Secondly, the reverse effect of technology transfer from universities and talent demand also affects regional innovation (Gong et al, 2020 ). In the process of technology transfer, in addition to financial returns, universities can also obtain further R&D information through market feedback channels to guide their scientific research activities and personnel training.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It can not only guide firms' technological innovation, but also stimulate their internal R&D investment enthusiasm and independent innovation capabilities. Secondly, the reverse effect of technology transfer from universities and talent demand also affects regional innovation (Gong et al, 2020 ). In the process of technology transfer, in addition to financial returns, universities can also obtain further R&D information through market feedback channels to guide their scientific research activities and personnel training.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, if firms over-rely on the transformation of innovation achievements, and fail to engage in the technological R&D process, it will be difficult to raise innovation levels, or even fall into innovation inertia, and the cycle of introducing, lagging, and reintroducing (Gong et al, 2020 ). Some scholars have found that the transformation of results in China's public sector comes with too much administrative intervention and lacks sufficient market-based operation to play a role in the technological progress of technology recipients (Huang and Chi, 2013 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The evidence showed that there is a feedback channel between university patent commercialization and knowledge innovation, and new knowledge generated by the interaction with the outside world in the process of patent commercialization was transmitted to the subject of knowledge innovation through this channel, forming a virtuous dynamic cycle (Gong, Nie, Peng, Peng & Liu, 2020). In this context, the Chinese Ministry of Education (MoE) and several education specialists and universities have started discussing the use of information and communication technology (ICT) to reform the entire educational system in the midst of this pandemic and provide online and distance learning instead, even with disrupted classes (Huang, Tlili, Chang et al, 2020).…”
Section: Effortsmentioning
confidence: 99%
“…Patent market operation and legal rights protection data are the research methods focused on evaluating the patents value in the eld of management [112]. Considering that universities produce a large number of patents every year, Gong [9] described the innovation value chain in terms of universities operating patents, and this study concluded that university patent commercialization activities can effectively feed back the innovation value of patents. Chen [10] used arti cial neural networks to explore the in uences of patent counts, defendant counts of patent litigation, and patent share on market value in the American semiconductor industry.…”
Section: Introductionmentioning
confidence: 99%